2012
DOI: 10.1371/journal.pone.0030561
|View full text |Cite
|
Sign up to set email alerts
|

Combinational Spinal GAD65 Gene Delivery and Systemic GABA-Mimetic Treatment for Modulation of Spasticity

Abstract: BackgroundLoss of GABA-mediated pre-synaptic inhibition after spinal injury plays a key role in the progressive increase in spinal reflexes and the appearance of spasticity. Clinical studies show that the use of baclofen (GABAB receptor agonist), while effective in modulating spasticity is associated with major side effects such as general sedation and progressive tolerance development. The goal of the present study was to assess if a combined therapy composed of spinal segment-specific upregulation of GAD65 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Although it may result in adverse systemic side effects and increasing tolerance during long-term treatment, it is evident that increasing inhibition in the spinal cord is an effective treatment for spasticity. Spasticity is associated with a decrease of inhibitory synapses and inhibitory post-synaptic potentials in motor neurons ( Kapitza et al, 2012 ; Kakinohana et al, 2012 ; Boulenguez et al, 2010 ) plus concurrent increase of excitatory synapses upon and persistent inward currents in motor neurons ( Tan et al, 2012 ; Toda et al, 2014 ; Bennett et al, 2001 ; Hultborn et al, 2013 ). We give evidence that there is an increase of vGluT1 boutons from proprioceptive afferents onto motor neurons and less presynaptic inhibition of proprioceptive afferents in the cervical spinal cord after bilateral pyramidotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it may result in adverse systemic side effects and increasing tolerance during long-term treatment, it is evident that increasing inhibition in the spinal cord is an effective treatment for spasticity. Spasticity is associated with a decrease of inhibitory synapses and inhibitory post-synaptic potentials in motor neurons ( Kapitza et al, 2012 ; Kakinohana et al, 2012 ; Boulenguez et al, 2010 ) plus concurrent increase of excitatory synapses upon and persistent inward currents in motor neurons ( Tan et al, 2012 ; Toda et al, 2014 ; Bennett et al, 2001 ; Hultborn et al, 2013 ). We give evidence that there is an increase of vGluT1 boutons from proprioceptive afferents onto motor neurons and less presynaptic inhibition of proprioceptive afferents in the cervical spinal cord after bilateral pyramidotomy.…”
Section: Discussionmentioning
confidence: 99%
“…This reorganization can involve maladaptation causing functional abnormalities such as spasticity. Proposed mechanisms of spasticity include increased activity and connectivity between proprioceptive Ia muscle afferents and motor neurons, reduced presynaptic inhibition of Ia afferents by spinal interneurons ( Toda et al, 2014 ; Kakinohana et al, 2012 ), reduced autogenic inhibition from Golgi tendon organs (via Ib afferents and inhibitory interneurons), reduced reciprocal inhibition by Ia afferents from antagonist muscles and modified excitation and inhibition from muscle spindle group II afferents reviewed in [ Nielsen et al, 2007 ; Dietz, 2002 ]) as well as intrinsic changes in motor neurons such as altered ion channels, serotonergic receptors and transporter concentrations in the membranes ( Boulenguez et al, 2010 ; Murray et al, 2011 ) and an increase in persistent inward currents in motor neurons ( Hultborn et al, 2013 ; Boulenguez et al, 2010 ; Bennett et al, 2001 ; ElBasiouny et al, 2010 ) which together cause an increase in motor neuron excitability.…”
Section: Introductionmentioning
confidence: 99%
“…While under specific pathological conditions (such as inflammatory or neuropathic pain) spinal GABA can have excitatory effects due to reduced expression of the potassium-chloride exporter KCC2 [75,76], systematic experimental but also clinical studies have demonstrated a potent anti-spasticity effect after intrathecal treatment with the GABA B receptor agonist baclofen, suggesting continuing inhibitory GABA B receptor-mediated action [77,78]. In addition, we have recently demonstrated an effective anti-spastic effect after spinal parenchymal GAD65 (glutamate decarboxylase) upregulation if combined with systemic tiagabine (GABA uptake inhibitor) treatment in animals with spinal ischemia-induced muscle spasticity [79]. Jointly, these data suggest the anti-spasticity effect observed in our current study can be mediated by a synaptically coupled GABA-inhibitory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Using this system coupled with rat models of spinal ischemic injury, L3 compression injury or spinal air-embolism-induced injury we have demonstrated the presence of velocity-dependent increase in muscle resistance which correlates with an increased EMG activity in gastrocnemius muscle [ 28 30 ]. In subsequent studies using the spinal ischemic model and spinal air embolism model of muscle spasticity we have demonstrated: i) a potent anti-spastic effect after spinal or systemic treatment with baclofen [ 31 ], tizanidine [ 32 ], NGX424 [ 13 ], ii) the effect of a combined anti-spastic therapy after spinal upregulation of GAD65 gene and systemic treatment with tiagabine [ 33 ], and, iii) development of baclofen tolerance in rats infused intrathecally with baclofen using a miniosmotic pump [ 34 ] and effective suppression of spasticity in baclofen-tolerant animals after systemic treatment with AMPA receptor antagonist NGX424 [ 35 ].…”
Section: Introductionmentioning
confidence: 99%